On some sequence sets based on Lucas band matrix and modulus functions - Hatim, Mustafa I.; Bektas, Cigdem A. (Univ Nis, Fac Sci Math, 2024)
In this study, the sequence sets & ell;(p)(G(k) , v, (E) over cap(r,s)) and & ell;(infinity)(G(k) , v, (E) over cap(r,s)) which are depended on the Lucas band matrix and a sequence of modulus functions, are presented. After that, a few inclusion relationships of these sequence sets are given. Furthermore, a geometrical property such as the modulus of convexity of the sequence set & ell;(p)(G(k) , v, (E) over cap(r,s)) is discussed.
Keywords: Lucas numbers; Modulus function; Sequence space; BK-space; Modulus of convexity